Robert Zougmoré interviewed by national TV of Senegal RTS1 - KINKELIBA - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
View the full version of Dr. Zourmoré's interview: http://www.youtube.com/watch?v=q7MB1muCDlc Regional Program Leader Robert Zougmoré, working for the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) from Mali Bamako, is being interviewed by the national TV of Senegal (RTS1) on CCAFS and its activities in Senegal. The topics that Robert discuss, in French, include seasonal forecasting in Kaffrine, partnership with national stakeholders such as Conference of African and French leaders of agricultural research institutes (CORAF), Institut senegalais de recherches agricoles, Le Centre de Suivi Ecologique (CSE) and others. The interview has been much appreciated by the Senegalese so that RTS1 broadcasted it several times